Función apelativa y recursos hiperbólicos en la traducción de los folletos turísticos - Marie-Ange Bugnot (Çédille: Revista de Estudios Franceses, 2006)
The tourist discourse features several vocative characteristics among which the hyperbole is one of the most relevant. The study of a reduced corpus of tourist texts enables us to analyse the richness of the hyperbolic elements usually found in this type of texts, both in the paradigmatic and syntagmatic selections as well as in their connection with the recurrent rhetorical devices. The hyperbole, thus, proves to be an essential element of cohesion to create a dreamlike reality.